Measurement of Ds+ production and nuclear modification factor in Pb-Pb collisions at √sNN=2.76 TeV - Adam, Jaroslav; Angelov, Venelin; Bock, Friederike; Busch, Oliver; Deisting, Alexander; Fleck, Martin; Glässel, Peter; Karayan, Lilit; Klein, Jochen; Klewin, Sebastian; Knichel, Michael Linus; Leardini, Lucia; et al. (Journal of high energy physics, 2016)
The production of prompt Ds+mesons was measured for the first time in collisions of heavy nuclei with the ALICE detector at the LHC. The analysis was performed on a data sample of Pb-Pb collisions at a centre-of-mass energy per nucleon pair, sNN$$ \sqrt{s_{NN}} $$, of 2.76 TeV in two different centrality classes, namely 0-10% and 20-50%. Ds+mesons and their antiparticles were reconstructed at mid-rapidity from their hadronic decay channel Ds+ → ϕπ+, with ϕ → K−K+, in the transverse momentum intervals 4 < pT < 12GeV/c and 6 < pT < 12 GeV/c for the 0-10% and 20-50% centrality classes, respectively. The nuclear modification factor RAA was computed by comparing the pT-differential production yields in Pb-Pb collisions to those in proton-proton (pp) collisions at the same energy. This pp reference was obtained using the cross section measured at s=7$$ \sqrt{s}=7 $$TeV and scaled to s=2.76$$ \sqrt{s}=2.76 $$TeV. The RAA of Ds+mesons was compared to that of non-strange D mesons in the 10% most central Pb-Pb collisions. At high pT (8 < pT < 12 GeV/c) a suppression of the Ds+-meson yield by a factor of about three, compatible within uncertainties with that of non-strange D mesons, is observed. At lower pT (4 < pT < 8 GeV/c) the values of the Ds+-meson RAA are larger than those of non-strange D mesons, although compatible within uncertainties. The production ratios Ds+/D0 and Ds+/D+ were also measured in Pb-Pb collisions and compared to their values in proton-proton collisions.
Im Titel ist "s" tiefgestellt und "+" hochgestellt
Im Titel ist "NN" nach s tiefgestellt, der ganze Ausdruck "s NN" steht unter dem Wurzelsymbol
ALICE collaboration: J. Adam, V. Anguelov, F. Bock, O. Busch, A. Deisting, M.G. Fleck, P. Glässel, L. Karayan, J. Klein, S. Klewin, M.L. Knichel, L. Leardini, J. Mercado Pérez, H. Oeschler, K. Oyama, Y. Pachmayer, F. Reidt, K. Reygers, R. Schicker, J. Stachel, J.H. Stiller, M.A. Völkl, D.F.Weiser, J. Wilkinson, B. Windelband, M. Winn, A. Zimmermann [und 955 weitere]
Gesehen am 30.07.2020